2019
DOI: 10.1016/j.htct.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic myeloid leukemia during pregnancy: a retrospective analysis at a single center

Abstract: We analyzed the management and outcomes of pregnancies of patients with chronic myeloid leukemia at a single center over fifteen years. Among the 203 CML female patients, there were ten pregnancies in seven women, all of them not planned. In three cases, the chronic myeloid leukemia diagnosis was made during pregnancy. Five patients received tyrosine kinase inhibitors in the first weeks of pregnancy and the drug was interrupted until delivery. One patient lost complete cytogenetic response, and two patients lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…De Moura et al reported that pregnant patients exposed to TKI in the first weeks of pregnancy exhibited no congenital malformations, but nevertheless recommended that TKI use be avoided during pregnancy. 44 Long-term imatinib use has been observed to cause vascular contraction in the placenta and shrinkage in the trophoblast layer both in rats receiving imatinib during pregnancy and also in rats in which imatinib use was stopped before pregnancy. 45 Normal births have been reported in association with the use of imatinib in the second and third trimesters of pregnancy, with lower concentrations of imatinib being observed in umbilical blood than in maternal blood.…”
Section: Discussionmentioning
confidence: 99%
“…De Moura et al reported that pregnant patients exposed to TKI in the first weeks of pregnancy exhibited no congenital malformations, but nevertheless recommended that TKI use be avoided during pregnancy. 44 Long-term imatinib use has been observed to cause vascular contraction in the placenta and shrinkage in the trophoblast layer both in rats receiving imatinib during pregnancy and also in rats in which imatinib use was stopped before pregnancy. 45 Normal births have been reported in association with the use of imatinib in the second and third trimesters of pregnancy, with lower concentrations of imatinib being observed in umbilical blood than in maternal blood.…”
Section: Discussionmentioning
confidence: 99%
“…In general, malignancies during the which are known to have functions that may be important on gonadal development, implantation and fetal development [5][6][7].…”
Section: Chronicmentioning
confidence: 99%